1999
DOI: 10.1007/s007840050093
|View full text |Cite
|
Sign up to set email alerts
|

In vitro cytotoxicity of resin-containing restorative materials after aging in artificial saliva

Abstract: Studies have reported that dental resin-based materials release substances which have biological liabilities. However, some current methods for detecting these substances may not be adequate to detect biologically relevant concentrations. In the current study, we hypothesized that resin-based materials exhibit cytotoxic effects and alter cellular function in vitro when high-pressure liquid chromatography (HPLC-UV detection) cannot detect any release of substances. We further hypothesized that this release cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
92
0
2

Year Published

2003
2003
2016
2016

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 125 publications
(98 citation statements)
references
References 26 publications
4
92
0
2
Order By: Relevance
“…11 The pH of the artificial saliva solution was adjusted to 6.7 with 10 N HCl, 10 and the solution was subsequently sterilized using single use filtration devices with a pore-size of 0.22 µm (Vacuflo, Schleicher & Schüll Microscience GmbH, Dassel, Germany). 12 All aging media were exchanged every week during the artificial aging period.…”
Section: Artificial Agingmentioning
confidence: 99%
“…11 The pH of the artificial saliva solution was adjusted to 6.7 with 10 N HCl, 10 and the solution was subsequently sterilized using single use filtration devices with a pore-size of 0.22 µm (Vacuflo, Schleicher & Schüll Microscience GmbH, Dassel, Germany). 12 All aging media were exchanged every week during the artificial aging period.…”
Section: Artificial Agingmentioning
confidence: 99%
“…One-component and onestep dentin bonding agents have been developed for easy application with the incorporation of the new monomers 2) . As the in vitro cytotoxicity of the resin monomers is reported in the studies [2][3][4][5][6][7] , there is concern about the biological safety of these materials. Dentin bonding agents may present different cytotoxicity by the interaction of the multiple components, thus the determination of the cytotoxicity of the product instead of the monomer is significant 3,8) .…”
Section: Introductionmentioning
confidence: 99%
“…The ormocer materials are considered amalgam alternatives or even fully adequate substitutes. 1,8 Laboratory studies on ormocer demonstrated good performance of the material with respect to polymerization shrinkage, 9 wear, 10 biocompatibility, 11 and marginal integrity. 12 Recently, nanofiller particles have been introduced in resin composite materials.…”
Section: Introductionmentioning
confidence: 99%